Evaluation and stance in war news : a linguistic analysis of American, British and Italian television news reporting of the 2003 Iraqi war - Haarman, Louann; Lombardo, Linda (London : Continuum, 2009)
'Evaluation and Stance in War News functions as a tool kit for the critical evaluation of language in the news, both as raw data in need of interpretation and as carefully packaged products of'information management' in need of'unpacking'. The chapters offer an array of theoretical and empirical instruments for revealing, identifying, sifting, weighing and connecting patterns of language use that construct messages. These messages carry with them world views and value systems that can either create an ever wider divide or serve to build bridges between peoples and countries.'--Jacket.
Includes bibliographical references (p. [195]-209) and index.
Keywords: Iraq War, 2003-2011 -- Mass media and the war; Television broadcasting of news -- United Kingdom; Television broadcasting of news -- Italy; Television broadcasting of news -- United States; Mass media and language -- United Kingdom; Mass media and language -- Italy; Mass media and language -- United States; Discourse analysis